A speed limit monetary policy rule for the euro area - Livio Stracca (European Central Bank (ECB), 2006)
This paper estimates a hybrid New Keynesian model on euro area data and evaluates the performance of different simple policy rules and of the optimal unconstrained rule under commitment. The study reaches two main conclusions. First, inflation is found to be mainly forward-looking in the euro area, which implies the optimal policy reaction to cost push shocks is a muted one. Second, a "speed limit" rule of the type recently proposed by Walsh (2003) is able to closely approximate the performance of the optimal rule under commitment. The optimal speed limit rule is also characterised by super-inertia, making it a first difference rule similar to those recently proposed as a possible solution to measurement problems in the level of the natural interest rate and of potential output.
Keywords: E52; E58; 330; commitment; euro area; hybrid New Keynesian model; monetary policy rules; speed limit policies; Eurozone; Geldpolitik; New-Keynesian Phillips Curve; Inflation; EU-Staaten